2022
DOI: 10.1007/s00540-022-03086-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 254 cesarean sections with COVID-19 in terms of anesthesia and clinical course: 1-year experience

Abstract: PurposeThe study aims to compare anesthesia methods, clinical course, and maternal and fetal outcomes of symptomatic and asymptomatic pregnant women undergoing cesarean operation with confirmed COVID-19. Methods 254 pregnant women with COVID-19 who had a cesarean section in our hospital between March 2020 and March 2021 were included in the study. Demographic information, laboratory test results, radiological data, treatments, anesthesia methods, and prognoses of the patients were evaluated retrospectively. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The results did not reveal significant differences in outcomes based on the chosen anesthesia method. Various confounding factors, such as fetal distress, deterioration of the mother’s health, catheter failure, and inappropriate timing of LMWH for regional anesthesia, contribute to the preference for general anesthesia over neuraxial anesthesia, making outcome comparisons challenging 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The results did not reveal significant differences in outcomes based on the chosen anesthesia method. Various confounding factors, such as fetal distress, deterioration of the mother’s health, catheter failure, and inappropriate timing of LMWH for regional anesthesia, contribute to the preference for general anesthesia over neuraxial anesthesia, making outcome comparisons challenging 37 .…”
Section: Discussionmentioning
confidence: 99%
“…NLR was studied in pregnant COVID-19 patients as well ( 74 , 75 ): Aydin Güzey et al ( 76 ) evaluated 254 cesarean sections with COVID-19 and found elevated levels of NLR among the symptomatic patients. Our research group also presented a case report where we found elevated NLR in a preeclamptic COVID-19 patient ( 77 ).…”
Section: Commentmentioning
confidence: 99%